2023
DOI: 10.1021/acs.langmuir.2c03283
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots Meet Enzymes: Hydrophobicity of Surface Ligands and Size Do Matter

Abstract: Colloidal quantum dots (QDs) are a class of representative fluorescent nanomaterials with tunable, bright, and sharp fluorescent emission, with promising biomedical applications. However, their effects on biological systems are not fully elucidated. In this work, we investigated the interactions between QDs with different surface ligands and different particle sizes and α-chymotrypsin (ChT) from the thermodynamic and kinetic perspectives. Enzymatic activity experiments demonstrated that the catalytic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…This was mainly because that larger Amsil had larger S t and could bind more taspase1 . Our group also found the same rule using CdSe quantum dots and chymotrypsin (ChT) as the object of study . However, Zhu et al found that smaller TiO 2 nanoparticles had stronger E on pepsin under the same mass concentration .…”
Section: Introductionsupporting
confidence: 58%
See 4 more Smart Citations
“…This was mainly because that larger Amsil had larger S t and could bind more taspase1 . Our group also found the same rule using CdSe quantum dots and chymotrypsin (ChT) as the object of study . However, Zhu et al found that smaller TiO 2 nanoparticles had stronger E on pepsin under the same mass concentration .…”
Section: Introductionsupporting
confidence: 58%
“…9 Our group also found the same rule using CdSe quantum dots and chymotrypsin (ChT) as the object of study. 8 However, Zhu et al found that smaller TiO 2 nanoparticles had stronger E on pepsin under the same mass concentration. 17 This could also be explained by S t .…”
Section: ■ Introductionmentioning
confidence: 98%
See 3 more Smart Citations